BENEFITS AND DRAWBACKS OF ONLINE LEARNING AMONG STUDENTS IN HIGHER EDUCATION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Online learning has transformed the educational landscape, providing flexibility, accessibility, and diverse learning opportunities for students worldwide. However, this approach also presents challenges such as limited social interaction, technical issues, and potential disparities in access. This article explores the benefits and drawbacks of online learning among students, supported by academic research and surveys. The findings highlight the dual nature of online education, emphasizing the need for balanced approaches to maximize its potential. The purpose of this study is to investigate the many advantages and disadvantages of online learning in the context of higher education. Students have the ability to access course materials and lectures in a convenient manner through online learning, which offers an incredible degree of flexibility. Non-traditional learners, such as working professionals or individuals with familial duties, who may have trouble attending conventional, face-to-face sessions, can benefit tremendously from the adaptability of online education. This is especially true for individuals who are non-traditional learners. It is also possible for students from a wide variety of backgrounds to pursue higher education through the use of online learning, which provides increased accessibility by bypassing regional geographical barriers.